Antimicrobial activity test of the crude extracts of some marine Mollusca against selected pathogenic fungi, in vitro - Dakhil, Zainab (University of Thi-Qar Journal of Science, 2019)
Crude extracts of marine Mollusca Sepia sp. ,Tibia insulaechorab-curta and Thais sp. marked as A, B and C respectively, using 50 % acetic acid were studied for their antifungal activity using agar well diffusion technique against seven fungi (Aspergillus niger, A. flavus, Candida albicans , C. krusei, C. tropicalis , C. famata & C. guilliermondii ). No antifungal activity was recorded against A. niger &A. flavus in all concentrations of Thais sp. extract. Sepia sp. & Tibia insulaechorab-curta extracts exhibited significant differences (P≥0.05) to good antifungal activity more than Thais sp. extract. An extract has been showed high activity against C. albicans (inhibition zone=27.6 mm) diameter, and minimum zone of inhibition (16mm) was recorded against growth A. niger of same extract. In B extract, maximum inhibition zone (26.6mm ) in growth A. flavus & C. albicans and minimum inhibition zone diameter (15mm) in growth A. niger .Also the minimal inhibitory concentration of all extracts were detected .The results showed the inhibition zones diameter of Fluconazole as positive control approximately with the inhibition zones of crude extracts .